Thermal Mapping in Flat Lowlands and Undulating Uplands – A Comparison of Results - Lauryna Šidlauskaitė; Jörgen Bogren (The Baltic Journal of Road and Bridge Engineering)
Thermal mapping has been known as a reliable technique to analyse and even predict road surface temperature in a stretch of road, rather than just a single point (e.g. road weather station location). The method itself was developed in the 1980s, and as time progressed, the technique was improved and has become more applicable. Due to other methods, such as climate modelling, becoming widely accessible and more affordable to apply, thermal mapping started being pushed out to the background as an expensive alternative. The idea for this paper arose from thermal mapping applications to Lithuanian roads that produced inconclusive results in some research areas and raised the question of whether this technique applies to flatlands as effectively as to uplands. The Czech Republic was chosen as a country with an available database and environmentally different road network. Several stretches of road thermal mapping data were analysed and compared. It was concluded, that in flat landscapes altitude has lesser predictability value for road surface temperature than in undulating uplands. In addition, thermal mapping results appear to be more inconclusive in flatlands, compared to uplands. Nevertheless, thermal mapping is a good and reliable method for determining cold spots.